A Population of Blue-Winged Macaw Primolius Maracana in Northeastern Brazil: Recommendations for a Local Conservation Action Plan. (September 2014) - Pichorim, Mauro; Câmara, Thanyria Pollyneide França; de Oliveira-Júnior, Tonny Marques; de Oliveira, Damião Valdenor; Nascimento, Érica Patrícia Galvão do; Mobley, Jason Alan
The Blue-winged Macaw ( Primolius maracana ) is currently classified as near threatened, and studies have shown a decrease in its population size in the southern and northeastern limits of its distribution over the last 50 years. In this study we assess the current status of a local population in Northeastern Brazil and propose a conservation action plan. We visited 56 l ocalities in the Serra de Santana mountain range to search for direct and indirect evidence of the species' presence or absence. We recorded P. maracana at 27 locations, restricted to two main areas (Pimenteira-Rio Fundo and Serra da Arara-Serra de São João). There was a positive correlation between the a ge of reported sightings a nd flock size (rs = 0.3; p = 0.02), suggesting a decreasing population size over the last several decades. P. maracana breeds during the rainy season (December-May) in this region, and nests were recorded in mulungus, cumarus and craibeiras trees. Based on soil use criteria, plant cover, fauna use, and indicator species, hillside habitats have been less impacted than flat areas in the upper highlands (mean conservation for high flat area = 5.8 ± 2.0 and for hill side areas = 8.0 ± 2.1; t 53 = 3.96, p < 0.01). The data indicate that Pimenteira-Rio Fundo and Serra da Arara-Serra de São João are priority areas for local conservation actions and that P. maracana is adapted to the hyper-xerophilous caatinga, and not restricted to the peripheral formations of this environment, as previously suggested. We propose measures to control the population decline, establish conservation units, implement tourism programs, adopt responsible environmental practices, and increase public awareness and mobilization. Such actions must be implemented by local government and civil society entities, university researchers, and landowners in order to be effective.